Aspekty przestrzenne i społeczne w odniesieniu do kształtowania środowiska mieszkaniowego w dużym mieście = Spatial and social aspects of creating the housing environment in big cities - Hnes, Ihor; Ivanochko, Ulyana (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Creating optimal conditions for individuals is essential in large cities. One of the factors promoting the balanced development of civilization is the attainment of social justice in societies, which is impossible if their members are not provided with an affordable and good quality housing. There exists a range of important parameters of the housing environment, regulated by project standards, that have a significant influence on the comfort, social and psychological health of inhabitants, housing safety, etc.
Keywords: budownictwo mieszkaniowe; bezpieczeństwo społeczne; budownictwo wielorodzinne; liczba kondygnacji; gęstość; mieszkania; czynsz; mieszkańcy; housing stock; social safety; revitalization; multi-family housing; height; compactness; flat; rent; inhabitants